New satellite attitude control structure using the geomagnetic field - Mohd Suhadis, Nurulasikin; Varatharajoo, Renuganth (Federation of Engineering Institutions of Islamic Countries, 2006)
The geomagnetic field is the main source of information considered when dealing with the magnetic attitude control system of a satellite. In this regards, the mathematical model of the geomagnetic field is described first in this paper.The simulation has been performed for the complex and simplified models, and the results show that the generated Earth’s magnetic field values are almost identical for both models. For demonstration purposes, the simplified model is chosen to simulate the attitude control system of the small satellite. The performance of the system exhibits that the attitude steady state error is achieved with values of ±0.5 degrees. Thus, the magnetic attitude control system is a promising option for small satellites.